Angiotensin-I Converting Enzyme Inhibitory Peptide Derived from Porcine Skeletal Muscle Myosin and Its Antihypertensive Activity in Spontaneously Hypertensive Rats - Katayama, K. (Institude of Food Technologists, 2007)
Crude myosin light chain was extracted from Japanese domestic pork loin and digested with pepsin. Antihypertensive peptide was isolated from this digest as a measure of its inhibitory activity for angiotensin-I con-verting enzyme (ACE). Through isolation with some chromatographies, a single active fraction was isolated, and it was detected as an octapeptide, Val-Lys-Lys-Val-Leu-Gly-Asn-Pro, from 47th to 54th positions of myosin light chain. The 50% inhibitory concentration of this peptide was 28.5 /iM. Kinetic evaluation showed that this peptide was a noncompetitive inhibitor, but it was slowly hydrolyzed by ACE. At the dose of 10 mg/kg, this peptide showed antihy¬pertensive activity after a maximum of 3 h of administration and was estimated as a temporally effective hypotensor.